Negotiation Behaviour And Their Outcome In Dyadic Business Negotiation Situation - Saw, Chee Wah (1995)
This research examine the differences between buyers and sellers on business negotiation behaviour, planning, frequency and outcome, besides examine the effects of cooperative behaviour, level of planning and frequency involvement on negotiation outcome. The negotiation outcome was measured by 3 factors: goal achievement, rate of settlement and perceived superior's approval.